Designing an analysis system for imaging process from bone scintigraphy as a potential predictor for validation of bone metastases - Herlina Zainal; Hanif Afkari; Alexander Agung; Gani Gunawan (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2021)
Cancer is a disease that is the leading cause of death worldwide. In 2012, there were 8.2 million deaths caused by cancer. Cancer suffered by patients can metastasize to other body parts, such as the lungs, liver, brain, and bones. The risk of bone metastases becomes higher after cancer has spread to other body tissues, so it is necessary to do more specific bone examinations. Bone scintigraphy is one of the applications from nuclear medicine that utilizes 99mTc radioactive material as a radio-pharmaceutical for bone scanning examinations. Bone scintigraphy is done to determine the presence of metastases in the bone caused by cancer. This bone scan is an image capture method with high sensitivity but has the disadvantage of not clearly distinguishing the presence of hotspots that appear due to metastases, trauma, or other abnormalities in the bones. This research aims to create an analysis system design based on image processing scripts using MATLAB. Medical physicists and nuclear medicine technicians can later use this system to conduct quantitative analysis as a reliable predictor system that validates visual analysis of hotspots suspected of being metastasis of cancer. Based on the result, prediction of the presence of bone metastasis by quantitative analysis using digital image processing techniques can be made. With a significance level of 5%, a prediction results using the analysis system design are compatible with the results of the diagnosis obtained from the medical record data of the patient of (85.67% ± 12.71%).